2009
DOI: 10.1143/jpsj.78.123708
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Energy Scales in Undoped YbRh2Si2Under Hydrostatic Pressure

Abstract: The temperature-magnetic field (T-H) phase diagram of YbRh 2 Si 2 in the vicinity of its quantum critical point is investigated by low-T magnetization measurements. Our analysis reveals that the energy scale T ? ðHÞ, previously related to the Kondo breakdown and terminating at 0.06 T for T ! 0, remains unchanged under pressure, whereas the antiferromagnetic critical field increases from 0.06 T (P ¼ 0) to 0.29 T (P ¼ 1:28 GPa), resulting in a crossing of T N ðHÞ and T ? ðHÞ. Our results are very similar to thos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 43 publications
17
49
0
Order By: Relevance
“…This finding is confirmed by a study on pure YbRh 2 Si 2 under physical pressure. 35) Also no relation between the second transition at T L and the T (B) line is evident as only for Yb(Rh 0.93 Co 0.07 ) 2 Si 2 T L vanishes in proximity to B line rendering this an accidental coincidence. With B assigned to the Kondo breakdown, we infer from B N > B that the magnetism extends into the regime where the Kondo effect is operating.…”
Section: Detaching the Af Instability And Kondo Breakdown By Chemicalmentioning
confidence: 97%
“…This finding is confirmed by a study on pure YbRh 2 Si 2 under physical pressure. 35) Also no relation between the second transition at T L and the T (B) line is evident as only for Yb(Rh 0.93 Co 0.07 ) 2 Si 2 T L vanishes in proximity to B line rendering this an accidental coincidence. With B assigned to the Kondo breakdown, we infer from B N > B that the magnetism extends into the regime where the Kondo effect is operating.…”
Section: Detaching the Af Instability And Kondo Breakdown By Chemicalmentioning
confidence: 97%
“…To understand non-universal NFL behaviors [2] in a unified way, dynamics of Kondo holes in a quantum critical system should be further investigated, since heterogeneous electronic states appear to be realized in a variety of correlated electron systems. For instance, it is interesting to ask what is the degree and influence of electronic heterogeneity in YbRh 2 Si 2 , particularly, given the nearly field-independent local to itinerant crossover in pressure tuned and Co-and Ir-doped YbRh 2 Si 2 [45,46]. Moreover, a dynamical electronic heterogeneity at a QCP accessed by an applied magnetic field was also revealed by NMR studies even in pure YbRh 2 Si 2 [47].…”
mentioning
confidence: 99%
“…The origin of the T Ã ðHÞ line is not clear at present. Recent experiments on YRS under pressure (12) or YRS doped with Co or Ir (13) have shown that while the critical field for the magnetic transition is found to shift, the T Ã line stays unchanged. This suggests that the T Ã feature is only weakly or not at all tied to the AFM transition.…”
mentioning
confidence: 99%